Expiration day - Powell, William Campbell (2014)
"It is the year 2049, and humanity is on the brink of extinction. Tania Deeley has always been told that she's a rarity: a human child in a world where most children are sophisticated androids manufactured by Oxted Corporation"--
"A Tom Doherty Associates book."
Keywords: Robots -- Fiction; Diaries -- Fiction; Science fiction; Robots -- Fiction; Coming of age -- Fiction; Diaries -- Fiction; England -- Fiction; England -- Fiction; Science fiction; Bildungsromans